2009
DOI: 10.1254/jphs.09196sc
|View full text |Cite
|
Sign up to set email alerts
|

The Pyrazolone Originally Reported to Be a Formyl Peptide Receptor (FPR) 2/ALX–Selective Agonist Is Instead an FPR1 and FPR2/ALX Dual Agonist

Abstract: Abstract. A pyrazolone compound acting as a formyl peptide receptor (FPR) 2/ALX-selective agonist has been reported, but its pharmacological activities on human FPRs (hFPRs) and mouse FPRs (mFprs) have not been well demonstrated. In this study, we found that this compound, designated as compound A, induced concentration-dependent calcium flux not only in Chinese hamster ovary (CHO) cells expressing hFPR2/ALX but also in cells expressing hFPR1, mFpr1, or mFpr2. It also induced the receptor internalization of hF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 12 publications
1
26
0
Order By: Relevance
“…Compound 43 (Cpd43) is a low MW compound synthesized as an agonist for FPR2 (Burli et al, 2006) and has been shown to have this function in human leukocytes (Sogawa et al, 2009;. In vivo, Cpd43 exerts anti-inflammatory effects in murine ear inflammation and air-pouch models, which require FPR2 (Burli et al, 2006;Dufton et al, 2010;Sogawa et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Compound 43 (Cpd43) is a low MW compound synthesized as an agonist for FPR2 (Burli et al, 2006) and has been shown to have this function in human leukocytes (Sogawa et al, 2009;. In vivo, Cpd43 exerts anti-inflammatory effects in murine ear inflammation and air-pouch models, which require FPR2 (Burli et al, 2006;Dufton et al, 2010;Sogawa et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…When investigated, the functional repertoire triggered by small non-peptide agonists such as the Quinazolinonoe (Quin-C1) derivatives that selectively bind FPR2 [15],AG14 that selectively binds FPR1 [16], and pyrazolone that binds both receptors [17], resembles that of the pro-inflammatory peptides and not that of the anti-inflammatory agonists. Using a chemolibrary screening approach it was recently shown that agonists of FPR1/FPR2 include compounds with wide chemical diversity [18].…”
Section: Introductionmentioning
confidence: 99%
“…19 It was reported that this compound did not show significant interactions with a series of unrelated protein targets, including CXCR2 and mitogen-activated P38a kinase. 20 In addition, the compound was orally active in mice.…”
Section: Discussionmentioning
confidence: 96%
“…We previously reported that Cpd43 has agonistic activities for mouse Fpr1 and Fpr2, with 50% effective concentration (EC 50 ) values of 0Á35 and 0Á89 lM, respectively, in aequorin assays measuring calcium mobilization (Table 1 and Sogawa et al 19 ). In this study, we first investigated whether Cpd43 would induce cross-desensitization in mouse neutrophils.…”
Section: Cpd43 Induces Cross-desensitization Of Intracellular Calciummentioning
confidence: 99%
See 1 more Smart Citation